Lexical Units Forming General Linguistic Picture of the World by Representing Culture of the Nation (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In this article, we analyze the “linguistic picture of the world, theoretical views of it, the relationship between language, culture and cognition. We also pay attention to the lexical units that show the linguistic landscape of the world in the language. In particular, we emphasize the use of idioms for different purposes.